Answer:
the answers are A, B, C.
The length of Carl's hair was 9 3/4 inches. After his hair cut, the length was 6 1/2 inches . How many inches did he cut?
Answer: 3 1/4 inches
Step-by-step explanation:
9 3/4 - 6 1/2
I turned 6 1/2 into an easier fraction so it can be easier to subtract. Now the expression is:
9 3/4 - 6 2/4
6 2/4 is equivalent to 6 1/2
I then got 3 1/4
Which value is a solution of (7)/(4)x^(2)-2=-0.5x+4? A.x=-2 B.x=-1 C.x=1 D.x=5
Answer:
The answer is A.
Step-by-step explanation:
Just answered the question
hardest question
X+X*94%=1164
X=?
Answer:
x = 600 and 1.94!=0
Step-by-step explanation:
Answer:
X = 600
Step-by-step explanation:
This is the answer because:
1) All you have to do is just isolate the variable by dividing each side by factors that don't contain the variable.
Hope this helps! :D
PLEASE HELP I WILL GIVE BRAINLIEST! if anybody can PLEASE make this circular flow model on paper and send me the picture but make it about AMAZON, that will be so appreciated!! thank you so much, it is due in an hour!
This it hope this helped :D
5 more than the product of 6 and a number 23. What is the number?
Answer:
x = 3
Step-by-step explanation:
Let x be the number
Write it out as an equation: 6x + 5 = 23Subtract 5 from each side, so it now looks like this: 6x = 18Divide each side by 6 to cancel out the 6 next to x. It should now look like this: x = 3
I hope this helps!
Find $\left[\left(\frac{2}{5}\right)^{12} \left(\frac{3}{16}\right)^{-8}\right] \cdot \left[\left(\frac{2}{5}\right)^{12} \left(\frac{3}{16}\right)^{-8}\right]^{-1}$
Answer:
1Step-by-step explanation:
Given the expression [tex]\left[\left(\frac{2}{5}\right)^{12} \left(\frac{3}{16}\right)^{-8}\right] \cdot \left[\left(\frac{2}{5}\right)^{12} \left(\frac{3}{16}\right)^{-8}\right]^{-1}[/tex]
According to indices:
[tex]a^{-1} = \frac{1}{a}[/tex]
Applying this to the question:
[tex]\left[\left(\frac{2}{5}\right)^{12} \left(\frac{3}{16}\right)^{-8}\right]^{-1} = \frac{1}\left\left(\frac{2}{5}\right)^{12} \left(\frac{3}{16}\right)^{-8}\right}[/tex]
Hence:
[tex]\left[\left(\frac{2}{5}\right)^{12} \left(\frac{3}{16}\right)^{-8}\right] \cdot \left[\left(\frac{2}{5}\right)^{12} \left(\frac{3}{16}\right)^{-8}\right]^{-1} = \frac{\left[\left(\frac{2}{5}\right)^{12} \left(\frac{3}{16}\right)^{-8}\right]}{\left[\left(\frac{2}{5}\right)^{12} \left(\frac{3}{16}\right)^{-8}\right]} \\\\\left[\left(\frac{2}{5}\right)^{12} \left(\frac{3}{16}\right)^{-8}\right] \cdot \left[\left(\frac{2}{5}\right)^{12} \left(\frac{3}{16}\right)^{-8}\right]^{-1} = 1[/tex]
Hence the right answer is 1
Answer:
= 1
Step-by-step explanation:
Can someone explain how to do this?
what is the volume the shapes
slope for (-3,-3) and (-5, -2)
Answer:
-1/2
Step-by-step explanation:
-3--2=-1 -3--5=2
-1/2
When graphed, the three lines y=-x + 2 y=2x-1, and y= x-2 intersect in such a way that they form a triangle.
What are the coordinates of the three vertices of this triangle?
.
-6
-5
3
1
2 3
4
5 6
7
3
4
-5
-6
OA (2.0), (0, 2), and (-1, -3)
ОВ. (0, 2), (2.0), and (1,-1)
2020 Edmentum. All rights reserved.
Answer:
the three vertices are (1, 1), (2, 0), (-1, -3).
The vertices of the triangles are the coordinates of the point of
intersection of the graph of the equation of the three lines.
Correct response:
The coordinates of the three vertices of the triangles are;
E. [tex]\underline{(2, 0), \ (1, -1), \ and \ (-1, -3)}[/tex]
How are the coordinates of the vertices obtained?The equation of the given lines are;
y = -x + 2, y = 2·x - 1, y = x - 2
The point of the intersection of the two lines, gives the vertices, and are
the solution of the two linear equations of the lines.
At the points where the lines intersect, we have;
-x + 2 = 2·x - 1
Which gives;
3·x = 3
x = 1
y = -1 + 2 = -1
A vertex is at the point (1, -1)
The coordinate of the second vertex is given as follows;
2·x - 1 = x - 2
2·x - x = -2 + 1 = -1
x = -1
y = -1 - 2 = -3
The second vertex is; (-1, -3)
The coordinates of the third vertex is given as follows;
-x + 2 = x - 2
2·x = 4
x = 2
y = 2 - 2 = 0
Which gives the point; (2, 0)
The three vertices are; E. (2, 0), (1, -1), and (-1, -3)Learn more about linear equations here:
https://brainly.com/question/1430935
PLS HELP AND GET RIGHT FOR BRAINLY AND 20 PTS
Mr. Fitch needs to get a loan to replace the air-conditioning system in his home. The cost of the replacement, including installation, is $4,348.00. He can apply for a 5- year loan or a 3-year loan. Both loans involve simple interest with an annual interest rate of 6.5%. If Mr. Fitch applies for the 5-year loan, how much more will he pay in interest than with the 3-year loan? F. $704.98 G. $565.24 H. $2,260.96 J. $56,524.00
Answer: g
Step-by-step explanation:
4348x.065=282.62
282.62x5=1413.1
282.62x3=847.86
1413.1-847.86=565.24
Compared to a 3-year loan he has to pay G. $565.24 more for a 5-year loan.
What is simple interest?We know simple interest (SI) is given by SI = (p×r×t)/100, where
p = principle, r = rate in percentage, and t = time in years.
Given, Mr. Fitch needs to get a loan to replace the air-conditioning system.
He can apply for a 5- year loan or a 3-year loan. Both loans involve simple interest with an annual interest rate of 6.5%.
Here, p = $4,348.00, r = 6.5%, t₃ = 3 and t₅ = 5.
For, t₃.
SI₃ = (4348×6.5×3)/100.
SI₃ = $847.86.
For, t₅.
SI₅ = (4348×6.5×5)/100.
SI₅ = $1,413.1.
So, the amount of interest he will have to pay more is (SI₅ - SI₃).
= $(1,413.1 - 847.86).
= $565.24.
learn more about simple interests here :
https://brainly.com/question/11564235
$SPJ2
10^2a=10^a-4
please help me solve this exponential problem
Answer: -4
Step-by-step explanation:
10^2a = 10^a-4
Ignore the base
2a = a - 4
2a - a = -4
a = -4
solve (2x+)x(6x^2-4x+3x^4)x(x-1)
Answer:
3x^6 -3x^5 +6x^4 -10x ^3 +4x ^2
Step-by-step explanation:
Remove the parentheses
Collect like terms
Reorder the terms
Hope this helped!
help me pls .. i appreciate it
how tall is the table
Answer:
I believe it's 105 cm.
Write each number in scientific notation.
1. 58,927
Answer:
58,927 converted to scientific notation is 5.8927 x 10^4 (10 to the fourth power
Step-by-step explanation:
Does this shape have rotational, reflection, both or none
42:11
What is the slope and the y-intercept of the line on the graph below?
-6-5-43
-2
3
4
-5
O slope = -4, y-intercept = 1
slope = -4, y-intercept
1
slope = -4 y-intercept = 1
Mark this and retum
Next
Submit
Answer:the answer should be B
Step-by-step explanation:
A sugar mixture has 3 parts water and 2 parts sugar. Suppose the chef adds one more part to each. What is the new ratio of sugar to water?
2 parts sugar to 4 parts water
3 parts sugar to 4 parts water
3 parts sugar to 3 parts water
4 parts sugar to 3 parts water
Answer: 4 parts sugar to 3 parts water would be the answer
Step-by-step explanation:
3 + 1 =4 and 2+1=3
4 parts sugar to 3 parts water is what i got correct on my test hope it helps
GOODLUCKKKKKKA truck can be rented from Company A for $130 a day plus $0.60 per mile. Company B charges $70 a day plus $0.90 per mile to rent the same truck. Find the number of miles in a day at which the rental costs for Company A and Company B are the same.
Answer:
200 miles
Step-by-step explanation:
Let's say that our variable is x, where x equals the amount of miles
Company A: a(x)=0.6x+130
Company B: b(x)=0.9x+70
For the first equation, you are charged 130 dollars, in addition to the 0.60 cents that you are charged per mile.
For the second equation, you are charged 70 dollars, in addition to the 0.90 cents that you are charged per mile.
You want to find how many miles it takes to make the two equations equal:
0.6x+130 = 0.9x+70 (Set them equal to each other because you are trying to find when the miles are equal and the cost is equal)
130=0.3x+70 (Subtract 0.6x from both sides)
60=0.3x (Subtract 70 from both sides)
x=200 (Divide both sides by 0.3 to find x)
Remember that x is the amount of miles, so, Company A and B would charge the same if you drove 200 miles.
Answer:I believe it’s 200 miles
Step-by-step explanation: let x represent the mileage you are trying to find and set the two equations equal to one another to find the mileage and which the rental cost would be the same.
130 + 0.60x = 70 + 0.90x
130-70 = 0.90x - 0.60x
60 = 0.30x
X= 60/0.03
X= 200 miles
Sally buys a hand bag. There was a discount
of 30%. If Sally paid $20, what was the original
price?
Answer: it is 29 dollars in total
Step-by-step explanation: hope its right, hope it helps, and ahve a good day!
If y varies directly as x and y = 208 when x = 16, what is the value of y when x= 11?
Ray AT bisects ZCAR, mZCAT = 5x and mZCAR = 9x + 7. What is mZ TAR?
A recipe asks that the following three ingridients be mixed together as follows add 1/2 of a cup of flour for every 1/2 of a teaspoon of baking soday and every 1/4 of a tea spoon of salt. A. 1 teaspoon of baking soda per 1 cup of flower B. 2 teaspoons of salt per 1 cup of flour C. 1 teaspoon of baking soda per 2 teaspoons of salt D. 1/2 teaspoon of salt per 1 teaspoon of baking soda E. 2 teaspoons of salt per 1 teaspoon of baking soda. Select all that apply.
Answer:
A and D are the only ones correct
Step-by-step explanation:
I did it
Answer: A D
Step-by-step explanation:
There u go
Which of the following equations have no solution? Check all that apply.
Lauren solved the equation - 3y - 18x = 12x - 21 for y and got y = 10x -
7 as the answer. Is this the correct answer?
O Yes
O No
Answer:
No, it's incorrect.
Step-by-step explanation:
The answer should be y = -10x + 7
3x^2 – 10x = 8
(it’s to the 2nd power btw)
Answer:
x = 4, (-2/3)
Step-by-step explanation:
3(x^2) – 10x = 8
3(x^2) – 10x - 8 = 0
(3x + 2)(x - 4) = 0
(3x + 2) = 0
3x = -2
x = (-2/3)
(x - 4) = 0
x = 4
Answer:
x = -2/3, 4
Step-by-step explanation:
move all terms to one side
3x^2 - 10x - 8 = 0
split the terms in 3x^2-10x-8 into two terms
3x^2+2x-12x-8=0
factor out common terms in first to and last to
x(3+2)-4(3x+2) =0
factor out common term 3x+2
(3x+2) (x-4)=0
solve for x
x=-2/3,4
What is the absolute value of 28?
Answer:
28
Step-by-step explanation: pls mark brainliest
A bag contains 15 marbles. The probability of randomly selecting a green marble is One-third. The probability of randomly selecting a green marble, replacing it, and then randomly selecting a red marble is StartFraction 1 over 15 EndFraction. What is the probability of randomly selecting a red marble
Answer:
1/5
Step-by-step explanation:
Total Number of Marbles in the bag = 15
The probability of randomly selecting a green marble is 1/3
The probability of randomly selecting a green marble, replacing it, and then randomly selecting a red marble = 1/15
The probability of randomly selecting a green marble, replacing it, and then randomly selecting a red marble is calculated as
The probability of randomly selecting a green marble × The probability of randomly selecting a red marble
Hence:
1/15 = 1/3 × R
1/15 = R/3
Cross Multiply
R × 15 = 1 × 3
R= 3/15
R= 1/5
Hence, the probability of randomly selecting a red marble is 1/5